What dimensions of women’s empowerment in agriculture matter for nutrition in Ghana? - Malapit, Hazel J.; Quisumbing, Agnes R. (Elsevier, 2015)
• Examines empowerment–nutrition links using a new survey-based empowerment measure. • Empowerment is more strongly associated with diet quality than nutrition status. • Credit decisionmaking is associated with better outcomes for both women and girls. • Different domains of empowerment may have different impacts on nutrition. This paper investigates linkages between women's empowerment in agriculture and the nutritional status of women and children using 2012 baseline data from the Feed the Future population-based survey in northern Ghana. Using a new survey-based index, the women's Empowerment in Agriculture Index, we conduct individual-level analyses of nutrition-related indicators including exclusive breastfeeding, children's dietary diversity score, minimum dietary diversity and minimum acceptable diet, children's height-for-age, weight-for-height, and weight-for-age z -scores, and women's dietary diversity score and body mass index. Results suggest that women's empowerment is more strongly associated with the quality of infant and young child feeding practices and only weakly associated with child nutrition status. Women's empowerment in credit decisions is positively and significantly correlated with women's dietary diversity, but not body mass index. This suggests that improved nutritional status is not necessarily correlated with empowerment across all domains, and that these domains may have different impacts on nutrition.